IMPLEMENTATION OF ONLINE PAYMENT SYSTEM AGAINST PAM TIRTA SALO KARAJAE ARREARS PAREPARE CITY - Ivana Triyulia; Syarifuddin Yusuf; Fajar Ladung (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2023)
Government Regulation Number 122 of 2015 concerning the Drinking Water Supply System states that clean water is household drinking water by going through various stages of changes in both the way of producing and without production which is then able to complete health requirements and can be drunk directly. This study aims to determine the implementation of the online payment system against PAM TirtaSaloKarajae arrears in Parepare City. The number of informants in this study amounted to 1 person using qualitative research methods with a case study approach. The data collection technique in this study is using interviews. This research was conducted by PAM Tirta Salo Karajae Parepare City with the research time starting from May to June which ranged from 2 months. The result of this research is that the implementation of an online payment system at PAM TirtaSaloKarajae Kota Parepare provides tangible benefits in terms of efficiency, convenience, and increased acceptance. In addition, cooperation with third parties and effective socialization are important factors in the success of this implementation. Thus, the use of an online payment system can be an effective solution in overcoming arrears and improving services for PAM Tirta Salo Karajae customers.